(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1973)
The three most used techniques for foecal examinations — the ones contributed by WLLIS 9 1921), FERREIRA et al.2 (1962) and HOFFMANN et al. 3 ( 1934) — were rather inadequate for this parasitiasis since they permitted, when applied simultaneously up to five times, diagnosis in wily 2 of 26 infested dogs, in 122 examined. The 26 uncovered cases (21,3%) were found through the application of the method described by Mello and Campos for the recovery of worms from gastrointestinal membranes in sacrificed dogs.